Golimumab: early experience and medium-term outcomes from two UK tertiary IBD centres. Issue 3 (11th October 2017) - Samaan, Mark A; Pavlidis, Polychronis; Digby-Bell, Jonathan; Johnston, Emma L; Dhillon, Angad; Paramsothy, Ramesh; Akintimehin, Abisoye O; Medcalf, Lucy; Chung-Faye, Guy; DuBois, Patrick; Koumoutsos, Ioannis; Powell, Nick; et al.
Abstract : Objective: To gain an understanding of the effectiveness of golimumab in a 'real-world' setting. Design: Retrospective cohort study using prospectively maintained clinical records. Setting: Two UK tertiary IBD centres. Patients: Patients with ulcerative colitis (UC) were given golimumab at Guy's & St Thomas and King's College Hospitals between September 2014 and December 2016. Intervention: Golimumab, a subcutaneously administered antitumour necrosis factor agent. Main outcome measures: Clinical disease activity was assessed at baseline and at the first clinical review following induction therapy using the Simple Clinical Colitis Activity Index (SCCAI). Response was defined as an SCCAI reduction of 3 points or more. Remission was defined as an SCCAI of less than 3. Results: Fifty-seven patients with UC completed golimumab induction therapy. Paired preinduction and postinduction SCCAI values were available for 31 patients and fell significantly from 7 (2–19) to 3 (0–11) (p<0.001). To these 31, an additional 13 patients who did not have paired SCCAI data but stopped treatment due to documented 'non-response' in the opinion of their supervising clinician, were added. Among this combined cohort, 23/44 (52%) had a clinical response, 15/44 (34%) achieved remission and 13/44 (30%) achieved corticosteroid-free remission. Faecal calprotectin and CRP fell (FC: pre-induction: 1096 (15-4800) μg/g, post-induction: 114 (11-4800) μg/g, p = 0.011; n = 20; CRP: pre-induction: 4 (1-59) mg/L, post-induction: 2 (1-34) mg/L, p = 0.01 for n = 43). Post-induction endoscopy was carried out in 23 patients and a mucosal healing (Mayo 0 or 1) rate of 35% was observed. Conclusions: Our experience mirrors previously reported real-world cohorts and demonstrates similar outcomes to those observed in randomised controlled trials. These data demonstrate a meaningful reduction in clinical, biochemical and endoscopic disease activity as well as a steroid-sparing effect in patients with previously refractory disease.